Lebar Nasofaring Pada Maloklusi Skeletal Kelas II Dan Skeletal Kelas I (Kajian pada Rekam Medik Pasien Ortodonti RSGM Fakultas Kedokteran Gigi Universitas Trisakti Tahun 2016-2017) - Yuniar Zen; salshabila Rahmania; Riko Nofrizal (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Backgrounds: Severe class II skeletal malocclusion could cause unfavorable facial appearance and impairments of mastication, swallowing, speaking, and breathing functions. Mouth breathing is one of the etiologies of malocclusion, caused by the narrowing of upper pharyngeal width. The aim of this study is to determine the upper pharyngeal width of class I and class II skeletal malocclusion. Materials and Methods: This study is an analytic observational method with cross sectional study design. Cephalogram samples are taken from patients of Trisakti University Dental Hospital in 2016-2017. The analysis is performed by measuring angles of SNA, SNB, ANB (class I, ANB: 2-4° and class II, ANB>4°), and upper pharyngeal width according to McNamara Analysis. Results: Average SNA angle is 8,40° (± 3,91), average SNB angle is 75,82° (± 3,62), average ANB angle is 4,58° (± 1,55), average upper pharyngeal width is 9,24 mm (± 2,20), average upper pharyngeal width of class I skeletal malocclusion group is 9,47 mm (± 2,37), and average upper pharyngeal width of class II skeletal malocclusion group is 9,01 mm (± 2,04). Conclusion: Average upper pharyngeal width of class I skeletal malocclusion is 9,47 mm (± 2,37) and average upper pharyngeal width of class II skeletal malocclusion is 9,01 mm (± 2,04).